The Usual Suspects? Productivity and Demand Shocks and Asia-Pacific Real Exchange Rates - Menzie David Chinn (Oesterreichische Nationalbank (OeNB), 1998)
The evidence for a productivity-based explanation for real exchange rate behavior of East Asian currencies is examined. Using sectoral output and employment data, relative prices and relative productivity levels are calculated for China, Indonesia, Japan, Korea, Malaysia, Philippines, Singapore, Taiwan and Thailand. Time series regressions of the real exchange rate on relative prices indicate a role for relative prices for Indonesia, Japan and Korea. When examining real exchange rates and relative productivity ratios, one finds a relationship for Japan, Malaysia, the Philippines. Only when augmenting the regressions with real oil prices significant relationships are obtained for Indonesia and Korea. Relative per capita income, a proxy for preferences towards services, does not appear to be an important determinant in this sample. Panel regression results are slightly more supportive of a relative price view of real exchange rates. However, the panel regressions incorporating productivity variables, as well as other demand side factors, provide less encouraging results, except for a subset of countries (Indonesia, Japan, Korea, Malaysia and the Philippines). Surprisingly, neither government spending nor the terms of trade appear to be a determinant of regional real exchange rates.
Keywords: F31; F41; 330; real exchange rate; productivity; tradables; nontradables; purchasing power parity